CHARACTERIZATION OF RHEOLOGICAL PROPERTIES OF SEMISOLID MATERIALS USED AS THERMAL INTERFACES. PART I: A BRIEF REVIEW - FLORINA-CARMEN CIORNEI; STELIAN ALACI (Journal of Engineering Studies and Research)
In optimizing the performances of electronic devices, the semisolids used as thermal pastes have a significant part. The interface material should have a good compliance to follow the shape of the contacting surfaces and higher spreadability but also, have increased filler content for high thermal conductivity. The properties of composite materials are theoretically modeled and for designing a semisolid the rheological characterization is required. The paper presents a concise review of the methods used in rheology for characterization of semisolids.